Towards a history of non-violence resistance - Hardiman, David (2013)
Following on from Gandhi, peace activists have created a large body of work on the strategy of non-violent protest that brings out both its strengths and advantages over and above violent insurrection. This literature has not, however, constructed a convincing history of the non-violent method. Most have depicted it as a timeless phenomenon, found in all historical societies in one form or another. Rather, it is, as this essay suggests, a method rooted in modernity, arising out of a particular strategic reaction to the coercive and legal apparatuses of the modern state. - Reproduced.
Keywords: Non violence